High Frequency Thermal Energy Harvesting Using Magnetic Shape Memory Films. Issue 17 (1st August 2014) - Gueltig, Marcel; Ossmer, Hinnerk; Ohtsuka, Makoto; Miki, Hiroyuki; Tsuchiya, Koki; Takagi, Toshiyuki; Kohl, Manfred
<x xml:space="preserve">Abstract</x> A new method for thermal energy harvesting at small temperature difference and high cycling frequency is presented that exploits the unique magnetic properties and actuation capability of magnetic shape memory alloy (MSMA) films. Polycrystalline films of the Ni50.4Co3.7Mn32.8In13.1 alloy are tailored, showing a large abrupt change of magnetization and low thermal hysteresis well above room temperature. Based on this material, a free‐standing film device is designed that exhibits thermomagnetically induced actuation between a heat source and sink with short heat transfer times. The cycling frequency of the device is tuned by mechanical frequency up‐conversion to over 200 Hz. An integrated pick‐up coil converts the thermally induced change of magnetization as well as the kinetic energy to electricity. For a temperature change of 10 K, the maximum peak power density is in the order of 5 mW cm‐3.